Updates on developing and applying biosensors for the detection of microorganisms, antimicrobial resistance genes and antibiotics: a scoping review - Magnano San Lio, Roberta; Barchitta, Martina; Maugeri, Andrea; La Rosa, Maria Clara; Favara, Giuliana; Agodi, Antonella (Frontiers in Public Health, 2023)
Background: The inappropriate use of antibiotics in clinical and non-clinical settings contributes to the increasing prevalence of multidrug-resistant microorganisms. Contemporary endeavours are focused on exploring novel technological methodologies, striving to create cost-effective and valuable alternatives for detecting microorganisms, antimicrobial resistance genes (ARGs), and/or antibiotics across diverse matrices. Within this context, there exists an increasingly pressing demand to consolidate insights into potential biosensors and their implications for public health in the battle against antimicrobial resistance (AMR). Methods: A scoping review was carried out to map the research conducted on biosensors for the detection of microorganisms, ARGs and/or antibiotics in clinical and environmental samples. The Preferred Reporting Items for Systematic reviews and Meta-Analyses extension for Scoping Reviews (PRISMA-ScR) checklist was used. Articles published from 1999 to November 2022 and indexed in the following databases were included: MEDLINE, EMBASE, Web of Science, BIOSIS Citation index, Derwent Innovations index, and KCI-Korean Journal.The 48 studies included in the scoping review described the development and/or validation of biosensors for the detection of microorganisms, ARGs and/or antibiotics. At its current stage, the detection of microorganisms and/or ARGs has focused primarily on the development and validation of biosensors in clinical and bacterial samples. By contrast, the detection of antibiotics has focused primarily on the development and validation of biosensors in environmental samples. Asides from target and samples, the intrinsic characteristics of biosensors described in the scoping review were heterogenous. Nonetheless, the number of studies assessing the efficacy and validation of the aforementioned biosensor remained limited, and there was also a lack of comparative analyses against conventional molecular techniques. Conclusion: Promoting high-quality research is essential to facilitate the integration of biosensors as innovative technologies within the realm of public health challenges, such as antimicrobial resistance AMR. Adopting a One-Health approach, it becomes imperative to delve deeper into these promising and feasible technologies, exploring their potential across diverse sample sets and matrices.